PHYTOCHEMICAL AND PHARMACOLOGICAL EVALUATION OF COMMIPHORA MUKUL FOR ANTIDEPRESSANT ACTIVITY IN ALBINO MICE - Pendyala, Vijetha; Janga, Ramesh Babu; Suryadevara, Vidyadhara (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The main aim and objective of the present study is to investigate the effect of Commiphora mukul (Family: Burseraceae), on depression in mice using tail suspension test (TST) and forced swim test (FST). Methods: The oleo-gum resin of guggul was extracted with alcohol and fractionated with ethyl acetate and petroleum ether. All the fractions were subjected for preliminary phytochemical screening, using various qualitative tests. Till date, no scientific data were available on the antidepressant activity of this plant. So, in the present investigation, TST and FST are selected as animal models for evaluation of antidepressant activity in albino mice. Results: The preliminary phytochemical screening of guggul has revealed the presence of carbohydrates, proteins, tannins, and flavonoids in hydroalcoholic fraction. Ethyl acetate fraction showed positive results toward flavonoids, alkaloids, proteins, and steroids. Hydroalcoholic, ethyl acetate, and petroleum ether fractions (50 and 100 mg/kg p.o.) of guggul administered orally for 14 successive days had decreased the immobility periods significantly in a dose-dependent manner in both TST and FST, showing significant antidepressant-like activity. The activities of the fractions were found to be comparable to imipramine in both FST and TST. Conclusions: Although a number of synthetic drugs are being used as standard treatment for clinically depressed patient, they have adverse effects that can compromise the therapeutic treatment. In the traditional systems of medicine, many plants and formulations have been used to treat depression for thousands of years. The results of this study indicate the potential for the use of guggul as an adjuvant in the treatment of depression. Keywords: Guggul, Commiphora mukul, Antidepressant activity, Forced swim test, Tail suspension test, Depression.